(untitled) (Latakia University Journal -Biological Sciences Series, 2017)
تم دراسة بعض الخصائص الفيزيائية والكيميائية لستة أصناف من القمح القاسي السوري (الوزن النوعي, وزن الالف حبة, رقم السقوط, البلورية, درجة اللون, حجم الراسب, محتوى الرماد, الرطوبة, البروتين, الألياف الخام, الجلوتين الرطب). أظهرت نتائج الاختبارات الفيزيائية أن كل الأصناف لها وزن نوعي عالي (75.18-84.4) كغ / ه ل, ووزن ألف حبة تراوح بين (34-44.5) غ. كما بينت نتائج الاختبارات الكيميائية أن جميع الأصناف كانت فيها نسبة البروتين عالية (13.63-14.28)%, وأن قيمة حجم الراسب كانت الأعلى في صنف شام 5 (39.67) مل والأقل في صنف حوراني (25.33) مل, بينما وجد أن صنف شام 7 كان الأقل بنسبة الرماد (1.15) % والألياف الخام (2.14)% ودرجة اللون (9.3). وجميع الأصناف كانت لها قيمة عالية في رقم السقوط (393- 550) ثا و تراوحت نسبة المادة الجافة بين (89.52 و90.89)%. وتراوحت قيم البلورية بين (85.5 و99) %. Some physical and chemical characteristics of six Syrian durum wheat genotypes were studied. (Test weight, 1000-kernel weigh, falling number, vitreousness, degree of color, sds ,ash, moisture, protein, crude fiber, wet gluten content). Results of physical characteristics showed that all genotypes had high test weight (75.18- 84.4) kg/ hl and 1000-kernel weight (34-44.5) g. The results of chemical characteristics indicated high percentage of protein in all genotypes (13.63- 14.28) %, the value of sds was highest in sham 5 (39.67) ml and lowest in al horani (25.33) ml. While be found Sham7 genotype was lowest in percentage of ash (1.15) % , crude fiber (2.14)%, and degree of color (9.3). All tested genotypes had high falling numbers (393-550 ) sec and high percentage of dry matter (89.52-90.89) %. Vitreousness values ranged between (85.5 and 99)%,